Reconstructing glacier mass balances in the Central Andes of Chile and Argentina using local and regional hydro-climatic data - Masiokas, Mariano Hugo; Christie, D. A.; Le Quesne, C.; Pitte, Pedro Miguel; Ruiz, Lucas Ernesto; Villalba, Ricardo; Luckman, B. H.; Berthier, E.; Nussbaumer, S. U.; González Reyes, A.; McPhee, J.; Barcaza, G.
Despite the great number and variety of glaciers in southern South America, in situ glacier mass balance records are extremely scarce and glacier climate relationships are still poorly understood in this region. Here we use the longest (> 35 years) and most complete in situ mass balance record, available for glaciar Echaurren Norte in the Andes at ~34° S, to develop a minimal glacier surface mass balance model that relies on nearby monthly precipitation and air temperature data as forcing. This basic model is able to explain 78 % of the variance in the annual glacier mass balance record over the 1978?2013 calibration period. An attribution assessment indicates that precipitation variability constitutes the most important forcing modulating annual glacier mass balances at this site. A regionally-averaged series of mean annual streamflow records from both sides of the Andes is then used to estimate, through simple linear regression, this glacier´s annual mass balance variations since 1909. The reconstruction model captures 68 % of the observed glacier mass balance variability and shows three periods of sustained positive mass balances embedded in an overall negative trend totaling almost −42 m w.eq. over the past 105 years. The three periods of sustained positive mass balances (centered in the 1920s?1930s, in the 1980s and in the first decade of the 21st century) coincide with several documented glacier advances in this region. Similar trends observed in other shorter glacier mass balance series suggest the glaciar Echaurren Norte reconstruction is representative of larger-scale conditions and could be useful for more detailed glaciological, hydrological and climatological assessments in this portion of the Andes. Fil: Masiokas, Mariano Hugo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. Provincia de Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales. ...